Orthopaedic rehabilitation of the athlete getting back in the game - Davies, George J.; Provencher, Matthew T.; Reider, Bruce (Philadelphia, PA Elsevier/Saunders, 2015)
Orthopaedic Rehabilitation of the Athlete was designed to be a comprehensive, extensively illustrated textbook about the rehabilitation of common musculoskeletal conditions that affect athletes-from the professional competitor to the occasional participant.
Shoulder instability -- Superior labral pathology (SLAP/long head biceps) -- Rotator cuff injuries --Acromioclavicular and sternoclavicular joint injuries -- Shoulder cartilage injuries, arthritis, and capsulitis -- Elbow and forearm injuries -- Wrist and hand injuries -- Lumbar spine injuries -- Thoracic spine injuries -- Hip/thigh muscle strains -- Femoroacetabular impigement -- Extensor mechanism injuries -- Meniscus injuries -- Articular cartilage injuries -- Ligament injuries -- Lower leg conditions -- Achilles tendon injuries -- Ankle injuries -- Foot injuries
Includes bibliographical references and index
CHK-1014g Donated by CD Books International, Inc
Keywords: Athletic Injuries -- rehabilitation; Recovery of Function; Orthopedic Procedures -- rehabilitation